2020
DOI: 10.1111/1742-6723.13541
|View full text |Cite
|
Sign up to set email alerts
|

Shetty test in ankle and foot trauma: An emergency department pilot study assessing specificity and sensitivity

Abstract: ObjectiveTo assess the potential impact of the Shetty test over Ottawa ankle foot rules (OAFR) on plain imaging utilisation in the ED.MethodsNursing and medical staff assessed both Shetty test and OAFR in ED. All patients received ankle and foot radiographs.ResultsFifty‐four participants were assessed. Shetty test specificity at triage was 0.40 (95% CI 0.25–0.57), compared to OAFR 0.10 (95% CI 0.03–0.24), McNemar's P < 0.01. Shetty test and OAFR sensitivity at triage was 0.92 (95% CI 0.64–0.99), McNemar's P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, previous studies related to the ST have primarily focused on the presence of fractures. [1][2][3]7 Therefore, the significant difference in the distribution of radiography findings observed in the current study could encourage the development of new scoring systems that incorporate both physical examination findings and the ST to determine fracture subtypes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, previous studies related to the ST have primarily focused on the presence of fractures. [1][2][3]7 Therefore, the significant difference in the distribution of radiography findings observed in the current study could encourage the development of new scoring systems that incorporate both physical examination findings and the ST to determine fracture subtypes.…”
Section: Discussionmentioning
confidence: 94%
“…The most common cause of ankle trauma in our study was determined to be sprain (65%), which is consistent with findings from similar studies that also identified sprains as the leading cause of injury. 2,21 It has been reported that in many healthcare institutions, ankle trauma patients are often sent directly to the radiography unit before undergoing a physical examination. 3,16,21,22 The aim of this study was to evaluate the diagnostic success of the ST in predicting fractures in pediatric cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the need for radiography in patients with acute ankle and foot trauma, various prediction rules have been developed. 5,6,7,8 The Ottawa Ankle Rules (OAR) is one of the internationally recognized prediction tools developed to evaluate these injuries in deciding on the need for radiographs. It is wellvalidated and has been included in many clinical practice guidelines worldwide.…”
Section: Introductionmentioning
confidence: 99%